2005
DOI: 10.1007/s10439-005-5564-7
|View full text |Cite
|
Sign up to set email alerts
|

Measurements and Theory of Normal Tracheal Breath Sounds

Abstract: We studied the mechanisms by which turbulent flow induces tracheal wall vibrations detected as tracheal breath sounds (TRBSs). The effects of flow rate at transitional Reynold's numbers (1300-10,000) and gas density on spectral patterns of TRBSs in eight normal subjects were measured. TRBSs were recorded with a contact sensor during air and heliox breathing at four flow rates (1.0, 1.5, 2.0, and 2.5 l/s). We found that normalized TRBSs were proportional to flow to the 1.89 power during inspiration and to the 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
21
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 14 publications
1
21
0
1
Order By: Relevance
“…Normal tracheal breath sound has a broad-band spectrum below 1000 Hz; it has been shown that its shape and spectral peaks change with the geometry and pathology of the upper airway, 3,4,12,16,24,28 while its amplitude and energy change with the amount of respiratory flow. 3,10,13,38 Based on these findings, several researchers have studied various features of tracheal sound for implementing acoustical respiratory flow estimation from tracheal sound. These features include sound's average power, 11,13,14,30,40 envelope, 26 entropy, 37 and mean frequencies.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Normal tracheal breath sound has a broad-band spectrum below 1000 Hz; it has been shown that its shape and spectral peaks change with the geometry and pathology of the upper airway, 3,4,12,16,24,28 while its amplitude and energy change with the amount of respiratory flow. 3,10,13,38 Based on these findings, several researchers have studied various features of tracheal sound for implementing acoustical respiratory flow estimation from tracheal sound. These features include sound's average power, 11,13,14,30,40 envelope, 26 entropy, 37 and mean frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies the relationship between tracheal sound and respiratory flow was studied extensively. 3,4,10,13,38 However, these studies were all focused on data of non-OSA individuals during wakefulness. When implementing acoustical respiratory flow estimation for sleep studies, it is important to note that the relationship between tracheal sound and respiratory flow may change when one sleeps; it may also be different in non-OSA and OSA individuals.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…6,7 Tracheal sounds originate from the vibrations of the tracheal wall and surrounding soft tissues caused by gas pressure fluctuations in the trachea. 8 The signals from a microphone or a piezo-electric film transducer placed over the trachea have been processed to monitor respiratory rate Received from the Department of Biomedical Engineering, College of Basic Medical Sciences, China Medical University, Shenyang, Liaoning, P. R. China, and the Department of Anesthesiology, University of Utah, Salt Lake City, Utah. Submitted for publication April 10, 2012.…”
mentioning
confidence: 99%